Television watching and cognitive outcomes in adults and older adults: A systematic review and dose-response meta-analysis of observational studies - Hattapark Dejakaisaya; Wiriya Mahikul; Nat Na-ek; Chanawee Hirunpattarasilp (PLoS ONE, 2025)
This systematic review and meta-analysis aimed to examine the association between television watching and cognitive outcomes in adults and older adults as the current evidence is inconsistent. We searched the Cochrane, MEDLINE, Embase, PsycINFO, Scopus, and Web of Science databases for relevant studies from inception to June 30, 2024. Risk of bias was assessed using the Newcastle–Ottawa Scale. Dose–response and conventional meta-analyses were performed using one-stage random-effects and DerSimonian and Laird random-effects models, respectively. Our systematic review included 35 studies with 1,292,052 participants (8,572 cases of cognitive impairment), of which 28 studies were further meta-analyzed. A dose–response meta-analysis revealed a nonlinear association between time spent watching TV and an increased risk of cognitive impairment (Wald test p-value = 0.04), particularly for viewing durations of ≥4 hours per day. Additionally, watching ≥6 hours of television per day was associated with a significant decrease in cognitive score (standardized beta coefficient = −0.09; 95% CI: −0.17, −0.003; I2 = 71.8%; seven studies). Also, a longer television-watching time was associated with a lower cognitive score (pooled standardized mean difference = −0.02; 95% CI: −0.03, −0.003; I2 = 66.45%; six studies). Watching television for a longer period was associated with negative cognitive outcomes in adults and older adults. Further research is needed to confirm this association and elucidate the underlying biological mechanisms.